Software development using C programming to calculate the cable weight in cable design / Robiah Embong - Embong, Robiah (2001)
The manual calculation performed during designing a cable can be difficult and may create errors. This paper describes developed software that is proposed to perform the calculation of the weight and earth fault current in cable design process. The developed software provides a more accurate and faster results compared to the manual method. The software is developed c programming.